EFEKTIVITAS PROGRAM PKH-LKP DALAM MEMBENTUK POTENSI WIRAUSAHA ALUMNI LEMBAGA PENDIDIKAN NONFORMAL (Studi Kasus di LPPK Palupi Madiun) - Windyaningrum, Theresia Liris (Widya Warta, 2014)
This study aimed (1) to determine the level of effectiveness of the program in terms of alumni who ran independent business or who worked at a customized fashion DUDI with existing standards and (2) to know the motivating factors that lead them to choose to work at DUDI and fashion tailoring entrepreneurship. This research made use of explorative descriptive method. The sample was obtained using census. The results showed that 10% of alumni of the 2011 program worked at DUDI fashion, which did not exist previously. Likewise, there was a 30% increase in the number of alumni of the 2011 program who ran independent business compared to those of the 2012 program (which was only 10%). While the number of alumni of the 2012 program who worked at DUDI did not change (namely 7%). But the number of alumni of the 2012 program who worked as entrepreneurs increased from 50 % to 64% .Although the capability of the alumni already met the standard of competence (being able to become assistants of apparel maker), the effectiveness of performance set by LPPK Palupi onthe 2011 program was only 71.43%. While, the achievement level of alumni of the 2012 program on both indicators set by the agent of LPPK Palupi was fulfilled 100%. The limitedcapability and nonpermanent income became the factors for the alumni to work at DUDI fashion rather than to work as entrepreneurs. While, the increase of income and unrestrictedtime of work due to the fact that the work could be done at home when doing some housework became the motivating factors for alumni to run fashion business after finishing the program.